Deconstructing the Privileged Status of Religion over the Status of Belief as the Root of Discrimination towards Kejawen Community - Wasisto, Muhammad Adiz (Jurnal Sosiologi Agama Indonesia (JSAI), 2024)
The Kejawen community, recognized as a belief system rather than a formal religion, faces systemic discrimination in Indonesia. This distinction underpins the country's recognition of its political and legal status, thereby impeding the rights of Indigenous practitioners, including Kejawen followers. Several factors contribute to this systemic discrimination: the Western conception of religion, the dichotomy between religion and belief enshrined in Article 29 of the 1945 Indonesian Constitution, the narrow definition of religion by the Indonesian Department of Religion, the association of indigenous beliefs with communism post-1965, and the application of blasphemy laws aimed at "purifying" religion while sidelining belief systems. This study aims to explore the discriminative dynamics against Kejawen within the binary framework of religion versus belief through qualitative research and critical discourse analysis. It seeks to uncover the ambiguity surrounding the concept of religion in Indonesia, drawing on a wide range of sources, including historical narratives, academic studies, relevant legislation, and judicial rulings. This research indicates a significant bias rooted in the differentiation between "religion" and "belief," primarily originating from Western perspectives on religion. This bias has led to the marginalization of Kejawen and other similar spiritual practices, which are often viewed as lesser compared to world religions.